Transformasi Makna Kosakata Bahasa Indonesia dalam Meme Instagram: Kajian Semantik Kontekstual - Malikha, Usrin (Universitas Al-Qolam Malang, 2025)
The shift in meaning of Indonesian vocabulary on social media, particularly in Instagram memes, reflects a dynamic linguistic phenomenon among teenagers. This study aims to describe the changes in vocabulary meaning in Instagram memes and analyze the contextual factors influencing these shifts. The research employed a qualitative descriptive method with contextual semantic analysis. Data consisted of 30 memes from five popular Instagram accounts, analyzed for vocabulary, visual context, and social interaction. The results indicate that vocabulary changes include generalization, specialization, amelioration, pejoration, and total transformation. Influencing factors include visual context, Generation Z creativity, digital social interaction, as well as humor and satire. These findings confirm that Instagram memes function not only as entertainment but also as a laboratory for vocabulary meaning change in Indonesian.